The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jhn.12906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of plasma 25‐hydroxyvitamin D on pulmonary function and exercise physiology in cystic fibrosis: A multicentre retrospective study

Abstract: Background A 25‐hydroxyvitamin D (25OHD) may exert immunomodulatory effects on respiratory health, which may translate to improvements in exercise physiology. Thus, we aimed to investigate whether plasma 25OHD is associated with lung function and aerobic fitness in people with cystic fibrosis (pwCF). Methods A multicentre retrospective review of pwCF (> 9 years old) attending the Royal Hospital for Sick Children (Edinburgh) or Wessex CF‐Unit (Southampton) was performed between July 2017 and October 2019. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore the associations between basal 25OHD concentration and pulmonary exacerbations (before vitamin D supplementation intake) is unknown. A single study performed by members of our group [43] reported a positive association between 25OHD and aerobic fitness measured using (Timmers, Stellato et CPET (VO 2peak ). Noteworthy, as all studies looking at 25OHD and lung health outcomes in cypCF are of epidemiological nature, these findings are not causal.…”
Section: Associations Of 25ohd Concentration With Lung Function Pulmo...mentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore the associations between basal 25OHD concentration and pulmonary exacerbations (before vitamin D supplementation intake) is unknown. A single study performed by members of our group [43] reported a positive association between 25OHD and aerobic fitness measured using (Timmers, Stellato et CPET (VO 2peak ). Noteworthy, as all studies looking at 25OHD and lung health outcomes in cypCF are of epidemiological nature, these findings are not causal.…”
Section: Associations Of 25ohd Concentration With Lung Function Pulmo...mentioning
confidence: 92%
“…Only one study (4.8%) [43] explored the relationship between 25OHD and aerobic fitness expressed as maximal aerobic fitness (VO 2peak ) in cypCF and reported a statistically significant association between 25OHD and VO 2peak (Table 4).…”
Section: Relationship Between 25ohd Concentration and Secondary Outco...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, targeted analyses were the most commonly applied approach for MS-based research in SES, with 52 human participant studies published. These experiments were predominantly performed in plasma 6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] or serum, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] with other biosamples mediums utilized such as urine, [51][52][53][54][55] fecal matter, 56,57 breath gases, [58][59][60][61][62][63] red blood cells, …”
Section: Targeted Analysismentioning
confidence: 99%
“…Vitamin D metabolites were a commonly investigated target in 2022, being investigated in six separate publications. 22,31,37,43,48,49 Three of these studies were cross-sectional in design, 22,31,37 with the remaining studies applying dietary and/or exercise interventions to target vitamin D status. 43,48,49 Vitamin D is a group of prohormones that play an important role in maintaining serum mineral status (notably calcium (Ca 2+ ) and phosphate (PO 4 − ) ions) which is integral to the formation and maintenance of bone mineral density.…”
Section: Vitamin Dmentioning
confidence: 99%